2022
DOI: 10.21831/jpai.v20i1.47519
|View full text |Cite
|
Sign up to set email alerts
|

Efek Gender, Kesulitan Akuntansi, Peluang Karir Dan Sindrom Impostor Terhadap Keputusan Mahasiswa Memilih Jurusan Akuntansi

Abstract: Penelitian ini bertujuan melihat serta membuktikan adanya efek dari gender, kesulitan akuntansi, peluang karir dan fenomena sindrom impostor terhadap keputusan mahasiswa dalam memilih jurusan akuntansi PTN atau PTS di Surabaya. Penelitian ini menggunakan metode kuantitatif memakai sumber data primer yang didapatkan dari menyebar kuesioner. Populasi penelitian ini merupakan mahasiswa akuntansi dan manajemen program S1 angkatan 2018 di Perguruan Tinggi Negeri Surabaya (UPN Veteran Jawa Timur) dan Perguruan Tingg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 8 publications
1
5
0
2
Order By: Relevance
“…There is no effect of gender on personal financial planning, or there are no differences in personal financial planning between students majoring in accounting; this could be because both male and female students have the same understanding of managing their finances. These results agree with research conducted by Helmy (2018), Soedradjat &Suryaningrum (2022), andSusilowati et al (2023). Helmy (2018) proves that there is no difference in ethical considerations between men and women.…”
Section: The Influence Of Gender Differences On Personal Financial Pl...supporting
confidence: 93%
See 1 more Smart Citation
“…There is no effect of gender on personal financial planning, or there are no differences in personal financial planning between students majoring in accounting; this could be because both male and female students have the same understanding of managing their finances. These results agree with research conducted by Helmy (2018), Soedradjat &Suryaningrum (2022), andSusilowati et al (2023). Helmy (2018) proves that there is no difference in ethical considerations between men and women.…”
Section: The Influence Of Gender Differences On Personal Financial Pl...supporting
confidence: 93%
“…Gender is an innate quality socially and culturally created in both men and women. The concept of gender refers to the variations in characteristics and qualities that occur periodically and vary across different locations (Soedradjat & Suryaningrum, 2022;Susilowati et al, 2023).…”
Section: Gendermentioning
confidence: 99%
“…In contrast, research conducted by Chotimah & Kartika (2017) states that female accounting students have better abilities than male accounting students when viewed from academic achievement, thus indicating that the condition of women is better than men and the results state that based on the results of the frequency distribution It was found that female auditors' audit judgment abilities were higher than male auditors (Sofia, 2022). In choosing accounting concentration studies, there are differences between men and women (Soedradjat & Suryaningrum, 2022). The research results by Friscilla & Nugroho (2020) prove significant differences between women and men in ethical behavior.…”
Section: Table Paired T-testmentioning
confidence: 99%
“…Gender is the difference and function of social roles constructed by society, as well as the responsibilities of men and women, so gender is not necessarily the same in different places and can change from time to time (Soedradjat & Suryaningrum, 2022;Susilowati et al, 2023). Meanwhile, sex/nature is gender, which consists of men and women, which God has determined.…”
Section: Gendermentioning
confidence: 99%
See 1 more Smart Citation